Synthesis of pyrrolo[3,2-d]pyrimidine-2,4(3H)-diones by domino C–N coupling/hydroamination reactions - Figueira de Abreu, Ruben Manuel; Tiedemann, Robin; Ehlers, Peter; Langer, Peter (Beilstein Journal of Organic Chemistry, 2025)
A variety of pyrrolo[3,2-d]pyrimidine-2,4(3H)-diones were prepared by a combination of Sonogashira reaction and subsequent cyclization by domino C–N coupling/hydroamination reaction. The optical properties (UV–vis absorption and fluorescence) depend on the substitution pattern of the compounds.
Keywords: alkynes; catalysis; cyclizations; domino reactions; heterocycles